Phototherapy for Cognitive Function in Patients With Dementia: A Systematic Review and Meta-Analysis - Zhu, Genying; Tong, Qifeng; Ye, Xiangming; Li, Juebao; Zhou, Liang; Sun, Peng; Liang, Feng; Zhong, Shuchang; Cheng, Ruidong; Zhang, Jie (Frontiers in Aging Neuroscience, 2022)
Background: Dementia is a major health burden worldwide. As numerous pharmacological trials for dementia have failed, emerging phototherapy studies have evaluated the efficacy of alternative therapies for cognition. Objective: To evaluate the association between phototherapy and changes in cognitive deficits in patients with dementia. Methods: PubMed, Embase, Web of Science, PsycINFO, CINAHL, and Cochrane Central Register of Controlled Trials were searched from inception to March 27, 2022. Inclusion criteria were controlled clinical trials of phototherapy interventions reporting pre-post changes in global cognitive function and subdomains in patients with dementia. Data were extracted by two independent reviewers and pooled in random-effects models. Subgroup and meta-regression analyses were conducted to investigate sources of heterogeneity. Results: Our analyses included 13 studies enrolling a total of 608 participants. Phototherapy showed significant associations with improvements of global cognitive function (standardized mean difference [SMD], 0.63; 95% confidence interval [CI], 0.33–0.94; P < 0.001) and subdomains, especially with respect to attention, executive function, and working memory. Near-infrared (NIR) light-emitting diodes (LEDs) photobiomodulation (SMD, 0.91; 95% CI, 0.46–1.36; P < 0.001) and lasers (SMD, 0.99; 95% CI 0.56–1.43; P < 0.001) showed more significant associations with improved cognitive functions when compared with normal visible light. In addition, the effect sizes of short-term effects (SMD, 0.63; 95% CI, 0.33–0.94; P < 0.001) were larger than effects assessed in long-term follow-up (SMD, 0.49; 95% CI -0.24–1.21; P = 0.189). Conclusions: In this meta-analysis, phototherapy interventions were associated with cognitive improvement in patients with dementia. NIR LEDs and lasers had advantages over normal visible light. Domain-specific effects were indicated for attention, executive function, and working memory. Short-term improvement after phototherapy was supported, while evidence for long-term benefits was lacking. Stronger evidence for individualized parameters such as optimal dosing is needed in the future.